Association between health-promoting lifestyle and electronic health literacy among Iranian university students - Yalda Mousazadeh; Parvin Sarbakhsh; Azizollah Arbabisarjou; Mohaddeseh Tolouei; Heydar Mousavi; Sahar Molaei (BMC Medical Education, 2025)
Abstract Background E-health literacy is the skill of searching, finding, understanding, and evaluating health information from electronic information sources and using this information to diagnose or treat a health disorder. Adequate health literacy results informed decision-making, and reduced health risks. This study aims to investigate the relationship between eHealth literacy and health-promoting behaviors among students at Khalkhal University of Medical Sciences. Method This descriptive-analytical study was conducted with students who were selected using a census method. Three questionnaires were used: a demographic questionnaire, the Norman and Skinner eHealth literacy questionnaire, and the Walker Health-Promoting Lifestyle Questionnaire. Data were analyzed using SPSS version 26. Pearson correlation coefficients, independent t-tests, and analysis of variance were employed for comparisons. Multiple linear regression models were used to examine the relationship between eHealth literacy and health-promoting lifestyle, adjusting for some demographic variables. Results A total of 255 participants were included in the study. The mean eHealth literacy score was 25.55 (SD = 6.4), and the mean health-promoting lifestyle score was 127.74 (SD = 23.59). There was a statistically significant difference in eHealth literacy scores based on economic status (P < 0.004). Pearson correlation analysis revealed a statistically significant correlation between the total eHealth literacy score and the health-promoting lifestyle score (r = 0.43, p < 0.001). According to the linear regression model, eHealth literacy significantly predicts health-promoting behaviors (β = 1.63, p < 0.001). Thus, each unit increase in eHealth literacy was associated with a 1.63 unit increase in the health-promoting lifestyle score. Conclusion The level of eHealth literacy and health-promoting lifestyle are both above moderate. Nevertheless, more work needs to be done to improve eHealth literacy, and health-related behaviors. It is recommended that new educational programs integrated into the curriculum for students including how to search the Internet, introduction to health-related databases, and a lesson on health-promoting behaviors.